2020
DOI: 10.1017/s1751731120000336
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of protein supplementation during late gestation of beef cows on maternal skeletal muscle and liver tissues metabolism

Abstract: Since nutritional requirements are increased at the end of gestation to meet the demands of the pregnant uterus, pregnant beef cows are susceptible to mobilization of body reserves (mainly fat and amino acids (AAs)) and to alter the metabolism of nutrients in the liver and muscle to support such demands. The objective of this study was to evaluate the effect of CP supplementation on maternal nutrient metabolism in the late gestation of beef cows grazing a low-quality pasture. Forty-three pregnant Nellore cows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 21 publications
1
13
0
4
Order By: Relevance
“…In the late pregnancy, when most studies used in this meta-analysis were concentrated, the bovine fetuses presented an accelerated growth [ 57 ], which resulted in greater glucose and amino acid (AA) demands to attend to the fetus’s anabolism and its oxidative metabolism [ 58 ]. Consistent with this, there is evidence that pregnant beef cows receiving a low-protein diet tended to have a higher circulating pool of total AA and a greater glycogenic AA blood concentration than pregnant cows fed with protein supplementation, indicating the greater skeletal muscle catabolism to attend the fetal demand in un-supplemented beef cows [ 40 ]. This pattern was associated with a lower ADG for cows under a low-protein nutritional plan.…”
Section: Discussionmentioning
confidence: 83%
“…In the late pregnancy, when most studies used in this meta-analysis were concentrated, the bovine fetuses presented an accelerated growth [ 57 ], which resulted in greater glucose and amino acid (AA) demands to attend to the fetus’s anabolism and its oxidative metabolism [ 58 ]. Consistent with this, there is evidence that pregnant beef cows receiving a low-protein diet tended to have a higher circulating pool of total AA and a greater glycogenic AA blood concentration than pregnant cows fed with protein supplementation, indicating the greater skeletal muscle catabolism to attend the fetal demand in un-supplemented beef cows [ 40 ]. This pattern was associated with a lower ADG for cows under a low-protein nutritional plan.…”
Section: Discussionmentioning
confidence: 83%
“…In growing animals, the rumen is the priority, therefore, only after supplying the N needs in the rumen is the supplementary N destined for anabolic functions (Batista et al, 2016). On the other hand, in pregnant cows the priority destination of available N seems to reside in the gestational tissues (Bell and Ehrhardt, 2000;Lopes et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal tissue mobilization or deposition occurs as a function of dietary substrate supplies (McNeill et al, 1997). Thus, nutritional adjustments for pregnant cows undergoing nutritional restrictions have been the subject of studies (Lopes et al, 2020), which, in general, aimed to establish nutritional management that minimizes lean tissue catabolism and the negative effects on the fetus. For instance, Lopes et al (2020) showed the importance of supplementation for undernourished beef cows and reported a tendency toward greater mRNA expression of skeletal muscle synthesis markers in cows that received protein supplementation during late gestation.…”
Section: Changes In Maternal and Placental Metabolism In Response To ...mentioning
confidence: 99%